Kai kurie eksperimentinės architektūros tipologinės raidos ypatumai - Grunskis, Tomas (Journal of Architecture and Urbanism, 2011)
Some peculiarities of typological development of experimental architectureIn continuation of his previously analyzed subject of experimental architecture, the article author discusses the development of this branch of architecture by describing the context of such development and its most prominent features and peculiarities. The article defines and suggests the general typology of experimental architecture, which summarizes examples of experimental architecture according to the character, function or purpose of experiment. The article also deals with foregrounding of socio-cultural aspect of experimental architecture development by relating it to different conditions and circumstances of the social – cultural context, which prevail in different periods of such architecture development. Besides, the author discusses the brandification process of experimental architecture, or, in other words, the regularities inherent to implementation of ideas and concepts of experimental architecture and their turning into architectural trademarks.Article in Lithuanian.Santrauka. Tęsdamas anksčiau nagrinėtą eksperimentinės architektūros temą, autorius straipsnyje aptaria šios architektūros srities raidą, apibūdindamas tiek tos raidos kontekstą, tiek ir ryškesnius jos bruožus bei ypatumus. Čia aptariama ir siūloma bendroji eksperimentinės architektūros tipologija, kuri apibendrina eksperimentinės architektūros pavyzdžius pagal eksperimentavimo pobūdį ir funkciją arba paskirtį. Taip pat straipsnyje aktualizuojamas sociokultūrinis eksperimentinės architektūros raidos aspektas, ją siejant su įvairiomis socialinio bei kultūrinio konteksto sąlygomis ir aplinkybėmis, būdingomis skirtingais šios architektūros rūšies raidos laikotarpiais. Be to, straipsnyje aptariamas eksperimentinės architektūros brandifikacijos procesas arba tai, kokie dėsningumai yra būdingi eksperimentinės architektūros idėjų ir koncepcijų įgyvendinimui bei jų virsmui architektūriniu prekiniu ženklu.Reikšminiai žodžiai: eksperimentinė architektūra, raida, tipologija, brandifikacija.First Publish Online: 22 May 2013